Application of Generalis and Specialists : Psycheducation Activities on Clients and Caregivers with Hipertension - Muhammad Ardianto Rodin; Herny Susanti; Ice Yulia Wardani (Jurnal Ilmu Keperawatan Jiwa, 2020)
Hypertension is a disease that causes emotional disturbances in individuals and the number one cause of death every year. Hypertension causes fatigue, headaches / heaviness in the nape of the neck, dizziness, blurred vision, palpitations, buzzing ears, and nosebleeds. Patients with hypertension who have poor lifestyle and bad coping tend to experience emotional disturbances so that feelings of tension, anxious thoughts, and physical changes such as increased blood pressure occur. Family Psychoeducation therapy is one of the elements of a family mental health care program by providing information and education through therapeutic communication. The purpose of this study is to determine changes in symptoms and the ability of clients and caregivers before and after being given the treatment of nurses and specialist nurses (psychoeducation) in treating clients with hypertension and care givers who also have hypertension. The case study method is used to determine changes in signs and symptoms in clients after nursing action. Case studies conducted on family dealing with hypertension (caregivers and clients) by providing general nurses and psychotherapy to caregivers in RW 05, Cibadak District, Bogor.  Result: signs and symptoms in hypertension and client anxiety decrease accompanied by an increase in the ability of clients and caregivers to overcome the problem of hypertension in caring for clients and themselves. Conclusion: involving caregivers who have the same disease as the client will help in reducing the signs and symptoms of hypertension that are shared between the client and caregiver.